Amorphous/crystalline ZrC alternating multilayers deposited by magnetron sputtering at room temperature. (September 2020) - Zhu, Ruihua; He, Huanhuan; Lin, Zhiwei; Jiang, Shengming; Zhang, Jian
Highlights: Amorphous/crystalline ZrC multilayer films were successfully prepared. Carbon atoms diffused and reacted with Zr to form crystal ZrC during deposition. A new mechanism for designing amorphous/crystalline multilayer films is proposed. Amorphous/crystalline ratio prepared in this mechanism can be controlled. Graphical abstract: Abstract: Multilayer films of alternating amorphous and crystalline layers have recently attracted research interest because they have the potential to suit an increasingly complex service environment. Amorphous zirconium carbide/crystalline zirconium carbide (a-ZrC/c-ZrC) multilayers with different layer thicknesses were prepared by magnetron sputtering at room temperature under 0.7 Pa Ar pressure. The microstructure of the multilayer film was analyzed by means of grazing incidence X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. The characterization results confirmed that the multilayer films were composed of alternating a-ZrC and c-ZrC layers. Carbon atoms diffuse into the crystalline zirconium (Zr) layer and react with Zr atoms to form crystalline ZrC during the sputtering process. This research indicates that it is feasible to prepare amorphous/crystalline multilayer films with expected modulation ratios and the same chemical composition by utilizing and controlling the high diffusion of specified atoms to react with certain layers.